High velocity proton collision with liquid lithium: a time dependent density functional theory study. Issue 13 (17th March 2017) - Bi, Gang; Kang, Jun; Wang, Lin-Wang
Abstract : Liquid lithium is often used as a coating material in fusion reaction chambers, where it is under constant bombardment from high speed neutrons and protons. Abstract : Liquid lithium is often used as a coating material in fusion reaction chambers, where it is under constant bombardment from high speed neutrons and protons. However, numerous fundamental questions are unanswered, for example whether a single proton impact can cause Li atom sputtering, and what is the electron excitation energy profile after a collision particularly for extremely high energy projectiles. Herein, we use a real-time dependent density functional method to study these questions for proton energies in the range of 30 eV to 1 MeV. The calculated stopping power agrees well with experiment, and it is found that the stopping power cannot be described by the single electron exciting spectrum based on the adiabatic eigen energies, and Li atom sputtering is not observed within our simulation time.